The Electrochemical Variation of a Kind of Protein Staining and Food Dye as a New Corrosion Inhibitor on Mild Steel in Acidic Medium - Demet Özkır (International Journal of Electrochemistry)
In this study, the relevance of a food dye, namely, Fast Green-FCF (FG-FCF), was surveyed as a new inhibitor for mild steel in HCl solution. This effect was specified by electrochemical impedance spectroscopy (EIS), one of the most widely used measurement techniques. As a result of the increment of the inhibitor concentration, it was seen that the values ​​of polarization resistance increased and covered the metal surface of FG-FCF like a blanket. Tests endorse that the FG-FCF is chemically adsorbed on mild steel surface, according to the Langmuir isotherm. With surface characteristic analyses, such as field emission scanning electron microscope (FESEM) and atomic force microscope (AFM), it was further determined that the metal surface in HCl of FG-FCF was protected. By applying the hydrogen gas evolution technique, FG-FCF has been proven to provide the lowest surface area with all inhibited solutions from the blank due to its strong adsorption to the metal surface. Finally, it has been clarified that FG-FCF can be practically used as a good corrosion inhibitor for mild steel with the supported results.